1999
DOI: 10.1073/pnas.96.6.2994
|View full text |Cite|
|
Sign up to set email alerts
|

Absence of tumor necrosis factor rescues RelA-deficient mice from embryonic lethality

Abstract: Mice lacking the RelA (p65) subunit of NF-κB die between days 14 and 15 of embryogenesis because of massive liver destruction. Fibroblasts and macrophages isolated from relA −/− embryos were found to be highly sensitive to tumor necrosis factor (TNF) cytotoxicity, raising the possibility that endogenous TNF is the cause of liver cell apoptosis. To test this idea, we generated mice lacking both TNF and RelA. Embryogenesis proceeds normally in such mice, and TNF/RelA double-deficient mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
186
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(195 citation statements)
references
References 46 publications
9
186
0
Order By: Relevance
“…25,26 Studies in knockout mice lacking NF-kB signalling components revealed an essential role of NF-kB in protecting the fetal liver from TNF-induced cell death. 21,22 We therefore hypothesized that the spontaneous apoptosis of NEMO-deficient hepatocytes that results in chronic hepatitis and HCC development in NEMO LPC-KO mice is driven by death receptor signalling. 27 Consistent with our earlier results showing that FADD deficiency could prevent spontaneous and LPS/TNF-induced apoptosis of NEMO-deficient hepatocytes, 15 we show here that LPC-specific ablation of FADD also prevents HCC development in NEMO LPC-KO mice demonstrating that FADD-dependent hepatocyte apoptosis is essential for hepatocarcinogenesis in this model.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Studies in knockout mice lacking NF-kB signalling components revealed an essential role of NF-kB in protecting the fetal liver from TNF-induced cell death. 21,22 We therefore hypothesized that the spontaneous apoptosis of NEMO-deficient hepatocytes that results in chronic hepatitis and HCC development in NEMO LPC-KO mice is driven by death receptor signalling. 27 Consistent with our earlier results showing that FADD deficiency could prevent spontaneous and LPS/TNF-induced apoptosis of NEMO-deficient hepatocytes, 15 we show here that LPC-specific ablation of FADD also prevents HCC development in NEMO LPC-KO mice demonstrating that FADD-dependent hepatocyte apoptosis is essential for hepatocarcinogenesis in this model.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion that ikkb 7/7 and rela 7/7 mice die from a common defect is supported by the ability of TNF receptor 1 and TNFa (Doi et al, 1999) null mutants, respectively, to block the embryonic lethality associated with the loss of IKKb and RelA. Consistent with a perturbation of TNFa signals leading to the death of ikkb 7/7 embryos, a weak induction of Rel/NF-kB in ikkb 7/7 mouse embryonic ®broblasts by TNFa establishes that proin¯ammatory cytokines induce Rel/NK-kB through IKKb and not IKKa Tanaka et al, 1999).…”
Section: Null Mutations For the Ikb Kinasesmentioning
confidence: 96%
“…rela 7/7 mice The absence of RelA leads to embryonic lethality between days E15 and E16 post-coitum, a result of fetal hepatocyte apoptosis (Beg and Baltimore, 1996). The death of rela 7/7 fetal hepatocytes arises from their heightened sensitivity to the cytotoxic e ects of TNFa, as evidenced by the observation that an absence of this cytokine rescues rela 7/7 mice from embryonic lethality (Doi et al, 1999). Consistent with RelA playing an anti-apoptotic role in di erent cell types, rela 7/7 ®broblasts and macrophages also exhibit increased sensitivity to apoptosis induced by TNFa (Beg and Baltimore, 1996).…”
Section: Null Mutations For Rel/nf-kb Proteinsmentioning
confidence: 99%
“…Moreover, embryonic lethality observed in RelA-/-mice also occurs in mice deficient in IKKβ or IKKγ [82,122]. The insult leading to liver apoptosis was shown to be TNF-α signaling in the developing liver, as crossing RelA-/-mice with either TNFα-/-or TNFR-/-mice rescued this liver phenotype [1,32]. Although TNF-α activates caspases responsible for the initiation and execution of apoptosis, the concurrent activation of NF-κB abrogates TNF-α's pro-apoptotic activity, because NF-κB also targets genes coding for inhibitors of caspase activation and apoptosis.…”
Section: Nf-κb and The Regulation Of Apoptosismentioning
confidence: 99%